Design and implementation of a power factor correction (PFC) circuit - 384599 Mohd. Rodhi Sahid (Skudai : Universiti Teknologi Malaysia, 2003)
Thesis (Master of Engineering (Electrical)) -- Universiti Teknologi Malaysia, 2003